Determinants of Student Learning Achievement (Case Study on Department of Physical Education Health and Recreation Students at Musamus University) - Ronald,; Hendra Jondry Hiskya,; Arifin Ika Nugroho,; Pricilya Margaretha Warwuru,; Febry Rahmadhani Suradji,; Nasiatul Aisyah Salim, (Technium Social Sciences Journal, 2023)
Education essentially aims to form fully qualified human resources. The quality of education is related to the learning process because the learning process is one of the most important aspects in the field of education. The purpose of this study was to determine the determinants of learning achievement in students of Physical Education, Health and Recreation at Musamus University. The population in this study were students of the Department of Physical Education, Health and Recreation, Musamus University, class of 2022. The sampling technique used was accidental random sampling. Data collection techniques were carried out using interviews. Data analysis techniques using descriptive statistical analysis and inferential statistical analysis. Based on the results of the analysis it was found that the learning achievement of Musamus University Physical Education Health & Recreation students was significantly influenced by all research variables (motivation, interest and talent).